The effect of cysteine mutations on recombinant deacetoxycephalosporin C synthase from S. clavuligerus. - Lee, H; Lloyd, MD; Harlos, K; Schofield, C (2000)
Cysteines 100, 155, and 197 of recombinant deacetoxycephalosporin C synthase were mutated to alanine residues. The C100A mutant had properties similar to those of the wild-type enzyme, but mutation of Cys-155 and Cys-197 reduced enzyme activity with penicillin N and penicillin G to different extents.